Od kluczowych kompetencji do przewagi konkurencyjnej - Roszyk-Kowalska, Gabriela (From core competences for competitive advantage, 2005)
Core competences decide about direction of development of enterprise, innovative, construction of competitive advantage. Valuable, rare and hard for imitation of specificity, but core competences are such, they allow to get competitive advantage. However, it does not identify majority enterprise domains, it owns core competences in which. Enterprise must remain in balance with enclosing, proficiently stock locate, and also use simultaneously deferring ability, who will allow to achieve superiority it. It is obliged to be based core competences on strategic plans of managements creation of this superiority.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 336-341